2018
DOI: 10.1021/acs.inorgchem.8b01778
|View full text |Cite
|
Sign up to set email alerts
|

Decisive Influence of the Metal in Multifunctional Gold, Silver, and Copper Metallacycles: High Quantum Yield Phosphorescence, Color Switching, and Liquid Crystalline Behavior

Abstract: Three cyclic trinuclear pyrazolate complexes with Au(I), Ag(I) or Cu(I) have been studied. These complexes have interesting and distinct optical and thermal properties depending on the metal, namely liquid crystalline behavior, red or deep-red phosphorescence at room temperature, thermoluminochromism and response to silver ions. The selected ligand, 4-hexyl-3,5-dimethylpyrazolate, maximizes the effect that the nature of the metals has on the properties of the complexes, thus allowing the intermolecular metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…Some Au(I) complexes exhibit AIE activity owing to an intermolecular interaction known as the aurophilic interaction 25,26 , in which a non-covalent Au-Au bond is formed between molecules. Because of this interaction, the luminescence of Au(I) complexes can be increased by aggregation in condensed phases [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . We hypothesised that the introduction of multiple aurophilic interactions could further enhance the AIE activity of Au complexes [36][37][38][39][40][41][42][43][44][45][46] and enable us to visualise a crystallisation process clearly.…”
mentioning
confidence: 99%
“…Some Au(I) complexes exhibit AIE activity owing to an intermolecular interaction known as the aurophilic interaction 25,26 , in which a non-covalent Au-Au bond is formed between molecules. Because of this interaction, the luminescence of Au(I) complexes can be increased by aggregation in condensed phases [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . We hypothesised that the introduction of multiple aurophilic interactions could further enhance the AIE activity of Au complexes [36][37][38][39][40][41][42][43][44][45][46] and enable us to visualise a crystallisation process clearly.…”
mentioning
confidence: 99%
“…Lintang et al reported that trinuclear group 11 metal pyrazolate complexes are phosphorescent chemosensors for the detection of benzene [5] (for two recent papers on photoluminescence of the Dias and Fujisawa groups see [6,7]). The Serrano group published several papers that describe compounds related to those discussed in the present paper but with interesting mesogen properties when the pyrazolate ligands have long chains in positions three and five and the metal is Cu, Ag or Au [8][9][10][11]. Cano's group published similar results for complexes with gold(I) [12].…”
Section: Introductionmentioning
confidence: 60%
“…Monitoring the excitation spectrum at 609 nm as the emission wavelength provides a peak at 278 nm, which is similar to its observed absorption spectrum. This result indicates a large Stokes shift from the difference of excitation and emission, originating from the excited triplet state of Au(I)-Au(I) bonding for phosphorescent metal complexes, which is also similar to the copper pyrazolate complex [12,15,31,32].…”
Section: Optical Properties Of Gold(i) Pyrazolate Complexmentioning
confidence: 72%